miR-576-5p Promotes the Proliferation of Papillary Thyroid Carcinoma through the MAPK4-AKT Pathway - Rui Hai; Yang Zhou; Fan Li; Qingxi Guo; Yang Long; Fang Wang; Lian Cheng; Fei Wu; Shi Chen; Xiangyu Zhou (International Journal of Analytical Chemistry)
Background. MicroRNA-576-5p (miR-576-5p) plays an important role in different human cancers. However, the biological function of miR-576-5p in papillary thyroid carcinoma (PTC) is still unclear. In this study, we explored the function and specific role of miR-576-5p in PTC. Methods. Expression levels of miR-576-5p in PTC patient tissues and cell lines were determined by reverse transcription-quantitative polymerase chain reaction (qRT‒PCR). Cell counting using cell counting kit-8 (CCK-8), wound healing, and Transwell assays were performed to evaluate the effect of miR-576-5p on the proliferation, migration, and invasion of TPC-1 cells. Expression levels of mitogen-activated protein kinase 4 (MAPK4) and phosphorylation levels of protein kinase B (AKT), extracellular regulated protein kinase (ERK), and P38 mitogen-activated protein kinase (P38) were detected by western blotting or immunohistochemistry (IHC). Results. The expression level of miR-576-5p in PTC tissues and TPC-1 cells was significantly increased. In vitro, overexpression of miR-576-5p promoted the proliferation, migration, and invasion of TPC-1 cells. In addition, MAPK4 was highly expressed in PTC tissues, and miR-576-5p could upregulate the expression of MAPK4. Interestingly, MAPK4 knockdown reversed cell proliferation but not migration and invasion in TPC-1 cells after miR-576-5p was overexpressed. Moreover, overexpression of miR-576-5p induced activation of the AKT pathway in TPC-1 cells, and MAPK4 gene knockout reversed this AKT pathway activation. Conclusion. In this study, we found that miR-576-5p was significantly overexpressed in PTC tissues and TPC-1 cells. In addition, miR-576-5p promoted the proliferation of TPC-1 cells by enhancing expression of MAPK4 and activating the AKT pathway.